Implementation of the ESC 0 h/1h algorithm and the HEART score in the emergency department: A prospective cohort study - Goaris W.A. Aarts; Cyril Camaro; Nina Vermaas; Jacky Kamps; Antonius E. van Herwaarden; Gilbert E. Cramer; Roland R.J. van Kimmenade; Niels van Royen; R.J.M. van Geuns; Peter Damman (International Journal of Cardiology: Heart & Vasculature, 2022)
Background: The European Society of Cardiology (ESC) 0 h/1h algorithm is the preferred diagnostic strategy for chest pain patients in the emergency department (ED). It is suggested that adding clinical information to the algorithm improves its diagnostic performance. This study evaluates implementation of the ESC 0 h/1h algorithm in the ED and investigates the potential advantages of combining it with a clinical decision rule, which might be especially relevant in the heterogenous observation category. Methods: In this prospective cohort study, chest pain patients in whom the ESC 0 h/1h algorithm was applied were enrolled. HEART score components were collected. Diagnostic characteristics were determined for the algorithm with and without addition of the HEART score. Primary endpoint was a composite endpoint at 30-day follow-up, consisting of myocardial infarction and death. Results: A total of 668 patients were enrolled. The rule-in and rule-out categories consisted of 8.2% and 54.9% of the patients, respectively. Positive predictive value and specificity of the rule-in category were 67.3% and 97.1%, respectively. Negative predictive value (NPV) and sensitivity of the rule-out category were both 100%. In the observation category, a HEART score ≤ 3 yielded a NPV and sensitivity of 97.1% and 93.8%, respectively. Conclusion: The ESC 0 h/1h algorithm yielded a NPV and sensitivity of 100% for myocardial infarction and death at 30-day follow-up. Addition of the HEART score did not provide clinically relevant advantages. Although the HEART score can be used to guide diagnostic testing in the observation category, a low HEART score did not yield an NPV of > 99%.